2013
DOI: 10.1371/journal.pone.0078488
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Microbial DNA Polymerase Activity Enables Detection and Growth Monitoring of Microbes from Clinical Blood Cultures

Abstract: Surveillance of bloodstream infections (BSI) is a high priority within the hospital setting. Broth-based blood cultures are the current gold standard for detecting BSI, however they can require lengthy incubation periods prior to detection of positive samples. We set out to demonstrate the feasibility of using enzymatic template generation and amplification (ETGA)-mediated measurement of DNA polymerase activity to detect microbes from clinical blood cultures. In addition to routine-collected hospital blood cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Although bacterial cultures are considered the reference method to determine the presence of microorganisms ( Zweitzig et al., 2013 ), molecular analysis is more sensitive, especially in anaerobic conditions, such as necrotized root canals ( Baumgartner, 2004 ). Particularly, Porphyromonas is considered fastidious genera and culture methods may underestimate their frequency ( Gomes and Herrera, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although bacterial cultures are considered the reference method to determine the presence of microorganisms ( Zweitzig et al., 2013 ), molecular analysis is more sensitive, especially in anaerobic conditions, such as necrotized root canals ( Baumgartner, 2004 ). Particularly, Porphyromonas is considered fastidious genera and culture methods may underestimate their frequency ( Gomes and Herrera, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…14,15 Because only 20% of all bacteria can be cultured using conventional techniques, it is not always easy to make a prompt and accurate diagnosis of cholangitis, although blood cultures can directly detect the organism causing cholangitis. Several studies showed that PCR-based methods were more sensitive than standard cultures for detecting translocated bactDNA in blood samples, [16][17][18] whereas, up to now, studies of bactDNA in patients with cholangitis have rarely been reported. We found that translocation of bactDNA is a frequent event in patients with cholangitis.…”
Section: Discussionmentioning
confidence: 99%